Variable Capital Structure Moderating Links Growth Opportunities, Investment Opportunity Sets, And Managerial Ownership to the Company's Value - Marjohan, Masno; ., Lativa; Kusmiati, Mia; Sampurnaningsih, Sri Retnaning (Journal of Posthumanism, 2026)
The purpose of the study is to analyze the influence of growth opportunities, investment opportunity sets, and managerial ownership on company value, with capital structure functioning as a moderator variable. A quantitative method using panel data regression analysis is applied. The study uses secondary data derived from the company's annual report. Sample of property development and operation subsector. Purposive sampling technique. The results of the study simultaneously, growth opportunities, investment opportunities, and managerial ownership have a significant influence on the value of the company. However, partial testing revealed that growth opportunities and investment opportunities had no significant effect, while managerial ownership showed a significant positive impact on the company's value. In addition, capital structures were found to significantly moderate the relationship between managerial ownership and company value, but did not moderate the relationship between growth opportunities or investment opportunities and company value.